Determinants of Unmet Needs Among Slovenian Old Population - Hlebec Valentina; Srakar Andrej; Majcen Boris (Sciendo, 2016)
Population ageing has significant effects on societies. The organization of care for dependent old people is one of the key issues for ageing societies. The majority of care for homebound dependent old people in Slovenia is still performed by informal carers, even though the use of formal services has been increasing over the last 20 years. The proportion and characteristics of people with unmet needs are important for the development of long term care social policy.